2001
DOI: 10.1029/2000ja000435
|View full text |Cite
|
Sign up to set email alerts
|

Special features of the September 24–27, 1998 storm during high solar wind dynamic pressure and northward interplanetary magnetic field

Abstract: Abstract. The geomagnetic storm on September 24 -27, 1998, was initiated by a sudden compression of the magnetosphere in response to the solar wind dynamic pressure pulse. Simultaneous with the pressure increase, the interplanetary magnetic field (IMF) became strongly northward. Several unexpected magnetospheric responses to this sudden impulse were observed. First, for • 30 min following the sudden impulse, the entire auroral oval became active and thick, while the polar cap area decreased to less than 1/2 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 49 publications
2
45
1
Order By: Relevance
“…Clauer et al (2001) reported an SC event with the largest amplitude in nighttime which occurred during a northward IMF turning. They treated the SC as a very special and unexpected event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clauer et al (2001) reported an SC event with the largest amplitude in nighttime which occurred during a northward IMF turning. They treated the SC as a very special and unexpected event.…”
Section: Discussionmentioning
confidence: 99%
“…Russell et al (1994) used the current system (1) and (2) in addition to the H -component reduction due to the en-hanced region-1 currents in the dayside in order to interpret the nighttime enhancement and daytime reduction of the SC amplitude for the southward IMF. Clauer et al (2001) proposed the enhanced region-1 current connected with the NBZ current system to explain the nighttime SC enhancement during the northward IMF turning.…”
Section: Discussionmentioning
confidence: 99%
“…Russell et al (1994b) also studied 7 SCs at the same stations during the southward IMF. The normalized amplitude showed the maximum in midnight and the minimums near 6 and 16 h LT. Clauer et al (2001) found an SC with the largest amplitude in midnight during a strong northward IMF turning and analyzed it as a special event. Although there is a discrepancy on IMF dependence of nighttime amplitude, above description indicates that the LT variation of SC amplitude does not depend much on longitude except the South Atlantic anomaly region.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth stressing that the longitudinal asymmetry pattern of the magnetic field reported by Clauer et al (2001) gives evidence of the PRC existence. Actually, ground-based measurements along the longitudinal chain of 19 mid-and low-latitude observatories showed that the magnetic field depression was not uniform around the Earth.…”
Section: Electric Fields and Field-aligned Currents In The Duskmentioning
confidence: 99%